Study of polycyclic aromatic hydrocarbon contamination of major rivers in the Czech Republic using biliary metabolite in chub, Leuciscus cephalus L - Blahova, Jana; Leontovycova, Drahomira; Kodes, Vit; Svobodova, Zdenka (Bulletin of environmental contamination and toxicology, 2013)
The aim of the present study was to evaluate polycyclic aromatic hydrocarbon (PAH) contamination of the major rivers in the Czech Republic using 1-hydroxypyrene (1-OHP) content in chub bile as a biomarker. The highest concentration of 1-OHP was found in the Otava River at Topělec (80.5 ng mg protein(-1)); the lowest content of 1-OHP was found in the Vltava at Zelčín (9.6 ng mg protein(-1)). At all sites, bottom sediment samples were collected and analyzed for PAH content. The PAH content ranged between 1.2 and 15.2 mg kg dry mass(-1) at all sites. Statistically significant positive correlations (p < 0.05) between biliary 1-OHP and sediment PAH content were found. Correlation coefficients for total and individual priority PAHs ranged from 0.63 to 0.77.
Keywords: polycyklické aromatické uhlovodíky; Pyrenes; Bile; pyreny; Environmental Monitoring; řeky; Polycyclic Aromatic Hydrocarbons; Biomarkers; zvířata; Rivers; monitorování životního prostředí; biologické markery; Czech Republic; Water Pollutants, Chemical; žluč; Animals; Česká republika; chemické látky znečišťující vodu; Cyprinidae